Peran media pembeljaran audio visual dalam meningkatkan minat belajar siswa pada mata pelajaran IPS MI/SD - enjel, enjel (AL-IHTIRAFIAH: JURNAL ILMIAH PENDIDIKAN GURU MADRASAH IBTIDAIYAH, 2023)
The purpose of this study was to determine the role of audiovisual learning media in increasing students' interest in learning social studies at SD/MI. This type of research is a qualitative research using a descriptive form. How to collect data using observation, interviews or questions and answers and documentation. Teachers and students of class VI are the subjects of this study. From the data analysis it was found that students' interest in learning increased by using audio-visual learning media. Students' interest in learning increased more than when they only used the lecture method.